Prognostic role of prognostic nutritional index in patients with bladder cancer: a systematic review and meta-analysis - Jing Sun; Zhenzhen Li; Xiaming Zhu (Frontiers in Oncology)
AimsAn increasing number of studies have explored the prognostic significance of the prognostic nutritional index (PNI) in bladder cancer patients, but the results are inconsistent. This study systematically investigates the prognostic value of baseline PNI in patients with bladder cancer through a meta-analytic approach.MethodsThe databases of PubMed, EmBase, and the Cochrane library were systematically searched for eligible studies from inception until April 2024. The prognostic outcomes including overall survival (OS) and recurrence-free survival (RFS). The summary outcomes were calculated using the random-effects model, and the exploratory analyses were performed by sensitivity and subgroup analyses.ResultsTwelve retrospective studies involved 2,951 patients with bladder cancer were selected in final analysis. The summary results found low PNI were associated with poor OS (HR: 1.80; 95%CI: 1.54-2.10; P<0.001) and RFS (HR: 1.53; 95%CI: 1.15-2.04; P=0.003). The association between low PNI and shorter OS was statistically significant in all subgroups. Additionally, the association between low PNI and RFS was also significant in most subgroups.ConclusionsThis study found a significant association between low PNI and poor prognosis in bladder cancer patients. Further large-scale prospective study should be performed to verify this association, and assess the nutrition interventions for patients with bladder cancer.Systematic review registrationhttps://inplasy.com/inplasy-2024-8-0020/, identifier INPLASY202480020.